2019
DOI: 10.1109/access.2019.2929535
|View full text |Cite
|
Sign up to set email alerts
|

Robustness and Edge Addition Strategy of Air Transport Networks: A Case Study of “the Belt and Road”

Abstract: Air transportation is of great importance in ''the Belt and Road'' (the B&R) region. The achievement of the B&R initiative relies on the availability, reliability, and safety of air transport infrastructure. A fundamental step is to find the critical elements in network performance. Considering the uneven distributions of population and economy, the current literature focusing on centrality measures in unweighted networks is not sufficient in the B&R region. By differentiating power and centrality in the B&R r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…e results were consistent with those of the previous studies where the nodes with high betweenness centrality were critical, especially in terms of shortest path length and global efficiency [43,44]. As for network robustness in the weighted approach, nodes ranking in recursive power sequence have been identified as critical in the preservation of network functionalities [23].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…e results were consistent with those of the previous studies where the nodes with high betweenness centrality were critical, especially in terms of shortest path length and global efficiency [43,44]. As for network robustness in the weighted approach, nodes ranking in recursive power sequence have been identified as critical in the preservation of network functionalities [23].…”
Section: Discussionsupporting
confidence: 90%
“…Recent measurements in a weighted approach have been conducted by considering link weight [20,21]. Other studies identified the key nodes through a weighted approach by introducing Bonacich power centrality [16], heterogeneous degrees [22], and recursive centrality and power [23]. However, what has rarely been noticed is the gap in the ability of weighted and unweighted approaches to preserve network functionalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, this measure has been widely used in different types of transport networks, including urban road networks (Sergio et al, 2006), subway networks (Vito and Massimo, 2002), and airline transport networks (Zhang et al, 2019). It suits the topic of this research well.…”
Section: Global Network Efficiencymentioning
confidence: 99%
“…Beyond these, a predominant focus has been on facilitating infrastructure connectivity which promotes the transport, energy, and communication infrastructure, forming a network connecting all the subregions within Asia and between the Asian, European, and African countries. Within this infrastructure connectivity, air-transportation infrastructure has linked even remote and inaccessible geographic locations and fostered intercity relations [2][3][4]. us, air transportation could immensely aid developing countries by unlocking the potential of trade and tourism.…”
Section: Introductionmentioning
confidence: 99%